Respuestas

2012-05-05T20:17:57+02:00

De lo expresado en el problema

\sqrt{A^{2}+A^{2}+2A^{2}cos\alpha} = 2(\sqrt{A^{2}+A^{2}-2A^{2}cos\alpha})

 

Elevando al cuadrado

A^{2}+A^{2}+2A^{2}cos\alpha = 4(A^{2}+A^{2}-2A^{2}cos\alpha)

 

Resolviendo

 

2A^{2}+2A^{2}cos\alpha = 4(2A^{2}-2A^{2}cos\alpha)\\ 2A^{2}(1 + cos\alpha) = 8A^{2}(1 - cos\alpha)\\ 1+ cos\alpha = 4-4cos\alpha\\ cos\alpha = \frac{3}{5}

 

El ángulo que cumple esta afirmación es 53º

 

cos53 = 3/5

 

ESPERO HABER AYUDADO

 

SALUDOS